Second-generation hexavalent molybdenum oxo-amidinate precursors for atomic layer deposition. Issue 4 (5th January 2017) - Jurca, T.; Peters, A. W.; Mouat, A. R.; Farha, O. K.; Hupp, J. T.; Lohr, T. L.; Delferro, M.; Marks, T. J.
Abstract : The synthesis and characterization of molybdenum oxo-amidinate ALD precursors MoO2 (R2 AMD)2 [AMD = N, N ′-di-R-acetamidinate; R = Cy (2 ; cyclohexyl) and i Pr (3 )] is reported. Abstract : The synthesis of molybdenum oxo-amidinate complexes MoO2 (R2 AMD)2 [AMD = N, N ′-di-R-acetamidinate; R = Cy (2 ; cyclohexyl) and i Pr (3 )], and their characterization by 1 H, 13 C NMR, X-ray diffraction, and thermogravimetric analysis is reported. Quartz-crystal microbalance and X-ray photoelectron spectroscopic studies confirm that3 is an improved ALD precursor versus the R = t -butyl derivative for MoO3 film growth. Complex3 is accessible in higher yields (80%+), is easier to handle without mass loss, and in conjunction with O3 as the second ALD reagent, yields nitride-free MoO3 films.